Effect of Reservoir Water Level Fluctuation on Stability of Earth-Fill Dam Slopes Using Coupled Seepage Stress Finite Element Modeling: A Case Study of Indonesian Volcanic Clay Dams - Komang Arya Utama; Widi Harwinsyah; Heru Tri Saksena (CV. Get Press Indonesia, 2026)
The structural integrity of earth-fill dams in Indonesia is increasingly challenged by reservoir water level fluctuations, particularly rapid drawdown triggered by irrigation demands and flood control. This study investigates the impact of water level changes on slope stability using coupled seepage–stress numerical modeling. The analysis was conducted on two representative dams within the Brantas and Citarum River Basin systems, characterized by high-plasticity clay cores, using secondary data from Ditjen SDA, PATGTL, and BMKG (2022–2024). Numerical simulations were performed using PLAXIS 2D. Results show that a drawdown rate of 0.5 m/day produces an 88% lag in pore water pressure dissipation, reducing the Factor of Safety (FoS) to 1.185, below the SNI 8064:2014 threshold. These findings highlight that transient hydro-mechanical effects significantly increase failure risk and are not captured by conventional methods. The study recommends limiting reservoir drawdown to a maximum of 0.4 m/day to maintain slope stability. Integration of real-time pore pressure monitoring into early warning systems is essential for improving dam safety management.